Adoption and standardization of attitude scale for polio framed on oversees population from underdeveloped area of West Bengal - Sen Gupta, Taniya; Malik, Atrayee; Ali, M. Afsar; Sikdar, Deb Prasad (International Journal Of Community Medicine And Public Health, 2023)
Background: Study revealed fear from polio vaccination programme yet not completely has eradicated from the minds of immigrated communities resides in backward areas of Bengal. Due that, pre-established attitude tool was adopted for the formation of new tool for targeted population. Methods: Interestingly, attitude tool found almost similar result after 5 years of its first administration (on minorities). Foundation of tool was set on 3-point Likert type scaling style. Classical test theory (CTT) was followed in which popularity index and discrimination index were taken for item-analysis for pilot study. Results: CTT rejects 6 items and test-retest reliability with high r value 0.94 suggests the tool has excellent reliability. Standardized tool finally comes in 31 items with 9 different dimensions. Conclusions: CTT method as handy method for small sample item-analysis where popularity index and discrimination index used to refine values on which item-total correlation was administered on Pearson’s correlation at 99% confidence interval. Application of the same tool after some years in CTT method in constructing attitude tool have successfully applied.